DUA JALAN PERCOBAAN UNTUK MENANGGAPI FUNDAMENTALISME AGAMA - Karlina Supelli (Jurnal Orientasi Baru, 2016)
Over the past decade, fundamentalism, conservatism, radicalism, extremism and terrorism have become the subject of a wide range of academic research. Against this backdrop, this article offers an epistemological analysis of fundamentalism that has rarely been examined. To complement the analysis, this article also looks as the ways in which information and communication technologies influence the patterns of contemporary terrorism. The author then discusses two experimental paths to respond to the challenges and problems raised by the rising tide of intolerance. Firstly, it is necessary to develop an integrated model of education, in which intellectual sharpness and moral sensitivity are complemented by emotional literacy. Secondly, it is possible to deconstruct absolutism in fundamentalist theology before countering with civic concepts. The first path requires a multidisciplinary approach which involves psychology, philosophical anthropology, theology and other sciences so as to unravel the ontology of emotion. The second path entails the openness of theologians towards deconstruction.